Ruth nengae Jonah ghae da kiki ri. - Wycliffe Bible Translators; Bible League ([S.l.] : Bible League : Wycliffe, 2009)
"The book of Ruth and Jonah in the Korafe language Oro province, Papua New Guinea" -- v. t.p.
"Korafe-Yegha"--Cover.
In Korafe-Yegha
Keywords: Korape language -- Texts; Papuan languages -- Texts; Papua New Guinea -- Languages -- Texts